2017
DOI: 10.1016/j.bbr.2017.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of GluA2 phosphorylation potentiates stress responsivity

Abstract: Cocaine addiction is characterized by persistent craving and addicts frequently relapse even after long periods of abstinence. Exposure to stress can precipitate relapse in humans and rodents. Stress and drug use can lead to common alterations in synaptic plasticity and these commonalities may contribute to the ability of stress to elicit relapse. These common changes in synaptic plasticity are mediated, in part, by alterations in the trafficking and stabilization of AMPA receptors. Exposure to both cocaine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…433 Caffino et al (2015) report that a single cocaine exposure in adolescent rats can reduce the 434 number of dendritic spines without any changes of GluA1 or GluA2 in the total mPFC 435 homogenate. Other studies employing the cocaine SA paradigm reported that disruption of 436 the GluA2 phosphorylation potentiated the acquisition of cocaine SA (Ellis et al 2017). In 437 the current work, the biochemical analysis yielded a sex × rearing interaction for the 438 GluA1, but any alteration induced per se by the drug exposure ( Figure 5A).…”
supporting
confidence: 44%
“…433 Caffino et al (2015) report that a single cocaine exposure in adolescent rats can reduce the 434 number of dendritic spines without any changes of GluA1 or GluA2 in the total mPFC 435 homogenate. Other studies employing the cocaine SA paradigm reported that disruption of 436 the GluA2 phosphorylation potentiated the acquisition of cocaine SA (Ellis et al 2017). In 437 the current work, the biochemical analysis yielded a sex × rearing interaction for the 438 GluA1, but any alteration induced per se by the drug exposure ( Figure 5A).…”
supporting
confidence: 44%
“…Caffino et al (2015) report that a single cocaine exposure in adolescent rats can reduce the number of dendritic spines without any changes of GluA1 or GluA2 in the total mPFC homogenate. Other studies employing the cocaine SA paradigm reported that disruption of the GluA2 phosphorylation potentiated the acquisition of cocaine SA (Ellis et al 2017). In was not certified by peer review) is the author/funder.…”
Section: Discussionmentioning
confidence: 98%
“…Epidemiologic studies showed that childhood adversity increased the risk of depression by 28.4% but also to illicit drug use by 16.5% (Anda et al 2006). Animal studies exploring how stressful situations influence addiction-like behaviours described that acute and chronic stress alters the phosphorylation of GluA2, affecting the function of the AMPA receptor but no the GluA1/GluA2 ratio in the nucleus accumbens and hippocampus (Ellis et al 2017;Caudal et al 2010;Caudal et al 2016). This evidence could explain why we not able to find differences in the GluA1/GluA2 ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Stress and drug use can lead to common alterations in synaptic plasticity that may contribute to the ability of stress to elicit relapse. For example, disruption of PKC-mediated GluA2 phosphorylation increases vulnerability to both SD-induced enhancement of social avoidance and stress-induced reinstatement of cocaine AA and CPP[ 258 ]. Study of resilience to the reinstating effects of SD stress may help to identify therapies that prevent stress-induced relapse.…”
Section: Resilience To the Effects Of Social Defeat On The Rewarding Properties Of Drugs Of Abusementioning
confidence: 99%